The impact of external factors on incomes of the state budget of Kazakhstan - Issakhova, A. S. (Journal of Economic Research & Business Administration, 2015)
Investigation of various factors on the revenues of the state budget can help to identify major flaws for solving urgent problems in the budgetary system of Kazakhstan and to achieve economic development in general, as the whole economic potential depends on the country’s budget. State budget revenues as an economic category is the object of the current study. Aim of this paper is to analyze the present status of state budget revenues and make a forecast on the impact of factors on its future. This article shows the concept of income budget in several aspects: as a material category, as a legal category and as an economic category. The dynamics of income and expenditure of the state budget are analyzed. Various factors affecting the state budget revenues are examined. The method of correlation and regression analysis is utilized. Most closely interlinked factors are identified and forecast on future periods is provided.